Ampullary cancer detected upon re‐examination in a patient initially diagnosed as cancer of unknown primary. Issue 3 (8th February 2022) - Kawamoto, Yasuharu; Ikezawa, Kenji; Hasegawa, Shinichiro; Wada, Hiroshi; Kudo, Toshihiro; Nagata, Shigenori; Ohkawa, Kazuyoshi
Abstract : In patients with cancer of unknown primary (CUP), the efficiency of reexamination in the improvement of the prognosis has not been demonstrated yet. In the present case, ampullary adenocarcinoma, initially diagnosed as CUP, was revealed by endoscopic forceps biopsy for the ampullary lesion progressing over time. Reexamination of the primary site in patients with CUP could contribute to better treatment options and improvement in the prognosis.